Augmented reality mobile application for Malay Heritage Museum - Haninah Masduki,; Siti Noor Aisyah Nazarrudin,; Siti Khadijah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Lack of staffs and language barriers are two factors that limit the Malay Heritage Museum UPM staffs to handle visitors especially during peak seasons. Therefore, an augmented reality mobile application is proposed to assists and entertain visitors while touring the museum. In this work, the augmented reality will be imposed at the Malay traditional cloth and textiles section. To develop the propose application, the methodology used in this work is agile model due to its capability to ensure that the overall process can be done within a time given and also its ability to increase the standard software instantly. Agile model consists of six phases such as requirements, design, development, testing, deployment and review. The experiment was conducted on the same day and three hours were allocated for the respondent because they were having classes. The time required for one respondent to experience the MTRACR is approximately 10 minutes per person. The survey is used as a platform to get feedbacks from users. Based on the survey, it shows that all users were satisfied with the proposed application and they suggested others to use it.